Factors Influencing the Design of Student Educational and Cultural Spaces and Buildings - Dmytrash, Olha (Theory and practice of design, 2022)
The publication is devoted to highlighting the main trends, patterns, and factors influencing the design of modern cultural and educational spaces and buildings at the premises of higher education institutions. Analogy, analysis and synthesis, comparison and generalization have been used in the study to establish the patterns and features of architectural and planning solutions. Collection and grouping of factors, development and testing of hypotheses, as well as evaluation of processes, have been used to study the building mass, features of classification and description of results. The analysis of the theoretical basis of designing cultural objects at universities shows that today this topic has been insufficiently covered in the domestic professional literature, which leads to the impossibility of implementing a positive world experience in Ukraine. The modern tendencies of the formation of effective and comfortable educational and cultural spaces of higher educational institutions have been characterized. The influence of architectural and spatial decisions on the efficiency and intensity of use of the realized cultural and educational premises and buildings within the universities has been estimated. The main directions of the formation of the functional content of students’ spaces and buildings are highlighted, namely: culture and education in free time. Behind each of these areas, there is a certain type of activity, a group of premises. The main factors influencing the design of cultural and educational institutions in the Free Economic Zone have been determined, which include: socio-economic, urban planning, architectural and spatial, and functional factors. It should be noted that the main criterion for the success of cultural and educational institutions in the free economic zone is the high intensity of their use, due to the involvement of food and drink venues in the group of main facilities. Besides, an important argument is daily access to facilities seven days a week, a large number of entrance spaces, and the use of training areas with flexible planning in the planning structure. In conclusion, it should be noted that educational and cultural spaces and buildings have the function of involving as many students as possible in university life, creating a close community of students and teachers, improving the image and establishing interuniversity and international relations.